Avaliação da resistência a flexão e do efeito da profundidade da cavidade e do armazenamento em água sobre a nanodureza de compósitos convencionais e bulk fill - Torres, Fellipe Bonisem (2017)
The use of Bulk fill composite resins has simplified the restorative procedures from incremental technique, with 2mm thick increments, to "Bulk" technique with 4 to 5 mm. The objective this study was the physical and mechanical characterization of the bulk fill compared as conventional. Through the flexural strength and evaluated effect of depth and water storage at nanohardness (HV) from 2 conventional composites (Filtek Z-350XT - Z350; GrandioSO-GSO) and 4 bulk fill (Surefill SDR® - SDR; Filtek Bulk Fill Flow-FBF, X-tra base-XTB, and X-tra Fil-XTF). The fist test, were in accordance with ISO 4049/2009 for flexural strength tests. Fifteen specimens (25mmX2mmX2mm) of each commercial brand, were made in a bipartite matrix, by photoactivation 1.200 mW/cm2 LED (Emitter C - Schuster) wet-grounded and stored in distilled water (37◦C/24-h) and stressed by three-point bending test (0.5 mm/min) until failure. The second evaluation of the effect of depth and water storage on the (HV) of the composites. were prepared cavities class II in Metallic molds (5,0 x 5,0 x 2,5 mm) The cavities were restored, five samples (n=5) for each composite were cured according to manufacturers’ instructions using Optilight Max® 1200mW / cm² (Gnatus). After storage in distilled water (37°C/ 24 h), was measured at a nanohardness using an DUH 211S, Shimadzu nanoindenter equipped with a Berkovich diamond tip (100nm radius). Each specimen was loaded with nine indentation at different depths ( three in each layer: superficial, 2mm and 4mm). Data from the two studies were submitted to Statistical analysis was done using a three-way analysis of variance (ANOVA) to determine the significance of the differences among the groups. A Tukey test was applied for pairwise comparisons (p,0.05). GSO presented the highest values of flexural strength , followed by XTB, XTF, Z350, FBF and. SDR had the lowest values. In the HV, there was an important difference between the surface and 4 mm for all composites, only SDR showed difference between 24h and 7d in 4mm, The performance of bulk fill composite in the tests of flexural strength and HV, has shown good results as reference their clinical indications, compared with conventional composites.